Community-based Strategies for Strengthening Science and Influencing Policy: Vernal Pool Initiatives in Maine - Jansujwicz, Jessica; Editor, Aram (Maine Policy Review, 2017)
Scientific research is not having the impact it could and should have on natural resources conservation. Rather than conceptualize and conduct research in isolation, we need new approaches to identify and investigate problems in coordination with stakeholders, policymakers, and others who would benefit from the research. By supporting partnerships between researchers and the public, citizen science creates new opportunities for stakeholders to interact with scientific experts. This process of public collaboration with scientists has far-reaching implications for science, management, and policy. Drawing on two decades of work on vernal pool management strategies in Maine, we illustrate how citizen science and engaged research helped bridge the science-policy gap. As scientists, we learned from diverse stakeholders at multiple levels of decision making, and this feedback led to improvements in our citizen science programs, gradual adaptations to our scientific research process, and locally based, innovative vernal pool policy initiatives.
Keywords: vernal pools; Maine; land use; science-policy gap; citizen science